Development of the Spiritual Dimension in Education - Qomariyah, Siti; Rosi, Mohammad; Tobi, Tobi; Hartono, Djoko; Taufikurrahman, Taufikurrahman (Universitas Trunojoyo Madura, 2025)
This research analyzes spiritual development in Islamic education through literature studies, examining its philosophical foundations and implementation at various levels of education. The content analysis uncovers key themes, research gaps, and modern challenges such as digitalization, AI, and technological ethical issues. The results show that Islamic education integrates spiritual, moral, and intellectual values through the principles of Tawheed, Tarbiyah, Tazkiyah, and Ta'lim, as well as the framework of Maqasid al-Sharia, with spiritual intelligence playing an important role in the emotional and moral development of students. The integration of spiritual values is effective through a holistic curriculum, regular activities, a supportive environment, and the role of educators. However, technology presents challenges related to privacy, algorithmic bias, and depth of spiritual experience, so digital ethics, pedagogical innovation, and educator competency enhancement are needed. The research emphasizes the need for measurable spiritual implementation models, comprehensive evaluation instruments, and follow-up studies to realize holistic and sustainable Islamic education.